Skateboarding LA : inside professional street skateboarding - Snyder, Gregory J. (New York : New York University Press, 2018)
Inside the complex and misunderstood world of professional street skateboarding. On a sunny Sunday in Los Angeles, a crew of skaters and videographers watch as one of them attempts to land a 'heel flip' over a fire hydrant on a sidewalk in front of the Biltmore Hotel. A staff member of the hotel demands they leave and picks up his phone to call the police. Not only does the skater land the trick, but he does so quickly, and spares everyone the unwanted stress of having to deal with the cops. This is not an uncommon occurrence in skateboarding, which is illegal in most American cities and this interaction is just part of the process of being a professional street skater. This is just one of Gregory Snyder's experiences from eight years inside the world of professional street skateboarding.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 28, 2018).
Keywords: Skateboarding -- California -- Los Angeles; Sport; Crime & criminology; Sports & active outdoor recreation; Rollerblading, skateboarding, etc